Os processos de ensino e de aprendizagem : a dimensão educativa na promoção do cuidado em saúde da pessoa idosa - Gehlen, Maria Helena (2019)
The purpose of this study was to analyze the teaching and learning processes developed by health professionals with the elderly in the multidimensional perspective in the promotion of health care. This is a qualitative study at the exploratory-descriptive level, with an approach to historical materialism and dialectical. It was carried out in the Nursing Practice Laboratory of the Franciscan University Center, in Santa Maria, RS, which integrates the teaching of the Nursing Undergraduate Degree with the Interdisciplinary Residency of Physical Rehabilitation. Seven health professionals and six elderly people participated in this study. The data were obtained through semi-structured interview and systematic observation, being analyzed according to the Content Analysis Technique. The project was approved by the Research Ethics Committee with registration number 2,202,003. Of the investigated findings, three categories were detected in the analysis, discussion and interpretation of the data, namely: teaching and learning in geriatric-gerontological care: an educational need in the promotion of health care; teaching and learning in geriatric-gerontological care: an educational possibility in the promotion of health care; and teaching of health professionals and the learning of the elderly in geriatric-gerontological care: an approximation between need and educational possibility. In the first one the visibility of the educative dimension to the health of the elderly person, as well as their aid in the promotion of the health care, in the maintenance of the basic activities of daily life, in the functionality and in the well-being of the elderly person. With the second, it is revealed the importance of effecting the educational dimension not only in discourses, but in practices and attitudes in everyday life. In the third category, we can see that there are interactions and associations that approximate the effectiveness of the educational dimension. It is necessary to rethink the complexity of the effectiveness of the teaching and learning processes of the elderly person, throughout their life in their daily lives, since teaching is to recreate collective strategies, with respect to autonomy, practices, knowledge and speeches, in communion with the several areas of geriatric-gerontological knowledge.